BnbHLH92a negatively regulates anthocyanin and proanthocyanidin biosynthesis in Brassica napus - Ran Hu; Meichen Zhu; Si Chen; Chengxiang Li; Qianwei Zhang; Lei Gao; Xueqin Liu; Shulin Shen; Fuyou Fu; Xinfu Xu; Ying Liang; Liezhao Liu; et al. (Crop Journal, 2023)
Yellow seed trait is a desirable characteristic with potential for increasing seed quality and commercial value in rapeseed, and anthocyanin and proanthocyanidins (PAs) are major seed-coat pigments. Few transcription factors involved in the regulation of anthocyanin and PAs biosynthesis have been characterized in rapeseed. In this study, we identified a transcription factor gene BnbHLH92a (BnaA06T0441000ZS) in rapeseed. Overexpressing BnbHLH92a both in Arabidopsis and in rapeseed reduced levels of anthocyanin and PAs. Correspondingly, the expression profiles of anthocyanin and PA biosynthesis genes (TT3, BAN, TT8, TT18, and TTG1) were shown by quantitative real-time PCR to be inhibited in BnbHLH92a-overexpressing Arabidopsis seeds, indicating that BnbHLH92a represses the anthocyanin and PA biosynthesis pathway in Arabidopsis. BnbHLH92a physically interacts with the BnTTG1 protein and represses the biosynthesis of anthocyanins and PAs in rapeseed. BnbHLH92a also binds directly to the BnTT18 promoter and represses its expression. These results suggest that BnbHLH92a is a novel upstream regulator of flavonoid biosynthesis in B. napus.